THE USAGE OF ENGLISH INTERNET SLANG AMONG MALAYSIANS IN SOCIAL MEDIA - Nor Azida, Sabri; Syazzim, Hamdan; Na-Thinamalar Magiswary, Nadarajan; R. S., Soo; Soo, Ruey Shing (2020)
Usage of social media among Malaysian keeps on rising day by day. Almost everyone in Malaysia owns a smartphone and with those smartphones, they can access social media such as WhatsApp, Instagram, Twitter, Facebook, and et cetera anywhere and anytime they want. With the existence of social media, a new style of writing was born and it is called internet slang. The researchers conducted this study to identify how frequently Malaysian use internet slang in daily online communication. This internet slang can damage the current vocabulary and vandalize the writing skills of a person. Researchers conducted documentary research by using the qualitative method to study and gain an understanding of internet slang used among Malaysian in social media. Researchers collect all 69 findings and evidence from posts on social media made by Malaysians. This study found that there are several types of internet slang that are commonly used among Malaysians on social media. Researchers suggest that Malaysian should limit themselves in using English internet slang in daily online communication as it can damage their writing style